Empowering Through Embodied Awareness: Evaluation of a Peer-Facilitated Trauma-Informed Mindfulness Curriculum in a Woman's Prison. (September 2019) - Rousseau, Danielle; Long, Nicole; Jackson, Elizabeth; Jurgensen, James
The cumulative effects of trauma, violence, and substance abuse both define women's pathways into the correctional system and contribute to their unique needs within it. This research offers a case study of the implementation of a gender-responsive, trauma-informed integrated mindfulness program within a women's prison. Applying a yoga-based psycho-educational approach, the manualized curriculum was presented in a 16-session, closed-group format with peer-facilitation and pre- and postprogramming assessments. Overall, outcomes of this study were promising. Program participants demonstrated improvements in the use of healthy coping skills, experience of traumatic stress, symptoms of anxiety and depression, self-compassion, sense of connection, ability to relate to others, emotional awareness, and self-regulation.